PENGARUH STRATEGI PEMBELAJARAN METAKOGNITIF TERHADAP KEMAMPUAN MEMECAHKAN MASALAH LINGKUNGAN DALAM PEMBELAJARAN SAINS - Tina Tina; Budiaman Budiaman; Uswatun hasanah (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
Sains is knowledge which universal and sistematic, also a collective knowledge of facts andconcepts. In this research was given a metacognitive strategies to student's environmental problemsolving in science learning. This research was aimed to find the effect of metacognitive strategies tostudent’s environmental problem solving in science learning. The population of this research wasKartika X-1 Junior High School’s students, and the sample were the seventh grade classes whichrandomly chosen. The data was collected by giving questionnaire about student's ability ofenvironmental problem solving for both of contol and experiment classes. The result were showed thatthe post-test average score of experiment class higher than the control class as much 34,37 > 24,00.The t-test showed that the result was significant at 0,000 > 0,005 which means that the metacognitivestrategies give positive effect to student’s environmental problem solving in science learning.